2015
DOI: 10.1007/s00702-015-1394-4
|View full text |Cite
|
Sign up to set email alerts
|

Staging of cognitive deficits and neuropathological and ultrastructural changes in streptozotocin-induced rat model of Alzheimer’s disease

Abstract: Immunohistochemistry and electron microscopy analysis were used to detect amyloid β-(Aβ 1-42 ) and hyperphosphorylated tau (AT8) accumulation and ultrastructural changes in the brain. Memory decline was time-(≤3 months/acute, ≥3 months/progressive) and STZ-icv dosedependent. Morphological changes were manifested as thinning of parietal cortex (≥1 month) and corpus callosum (9 months), and were more pronounced in the 3 mg/kg STZ group. Early neurofibrillary changes (AT8) were detected from 1 month onward in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
96
1
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 118 publications
(120 citation statements)
references
References 96 publications
15
96
1
8
Order By: Relevance
“…Literature data indicate that iron-induced oxidative stress inactivates IDE (Shinall et al 2005) which might provide an explanation why iron-chelators like M30 could have beneficial effect at the level of IDE, as detected in our experiments for the first time. Decreased IDE protein and gene expression has been found in STZ-icv rat model also by others (Yang et al 2014), but our recent 9-month follow up data on staging of cognitive, neuropathological and neurochemical changes in STZ-icv rat model has shown that the order of pathology appearance after STZ-icv treatment is: tau protein/2 weeks, IDE/1 month, and amyloid β/3 months (Osmanovic Knezovic et al 2015), which supports the results presented here.…”
supporting
confidence: 92%
“…Literature data indicate that iron-induced oxidative stress inactivates IDE (Shinall et al 2005) which might provide an explanation why iron-chelators like M30 could have beneficial effect at the level of IDE, as detected in our experiments for the first time. Decreased IDE protein and gene expression has been found in STZ-icv rat model also by others (Yang et al 2014), but our recent 9-month follow up data on staging of cognitive, neuropathological and neurochemical changes in STZ-icv rat model has shown that the order of pathology appearance after STZ-icv treatment is: tau protein/2 weeks, IDE/1 month, and amyloid β/3 months (Osmanovic Knezovic et al 2015), which supports the results presented here.…”
supporting
confidence: 92%
“…In comparison to AD, in VaD, human brain neurotransmitter alterations are mild, e.g., for choline acetyltransferase activity, muscarinic receptor density, serotonin, dopamine, homovanillic acid, dopamine D1-and D2-receptor density, noradrenaline, and gamma aminobutyric acid (GABA), while 5-hydroxyindoleacetic acid (5-HIAA) shows a more pronounced deficiency. This data summarized here agree in principle with more recent conclusions of post-mortem human brain studies and experimental models (Ohara et al 1994;Pimlott et al 2004;Jia et al 2004;Tohgi et al 1996;Chen et al 2013;Lee et al 2014;Niwa et al 2002;Pedrós et al 2014;Knezovic et al 2015;Barilar et al 2015). CSF concentrations of choline were significantly higher in VaD patients compared to AD and controls but did no correlate with mini-mental state examination (MMSE) scores (Jia et al 2004;Tohgi et al 1996).…”
Section: Pathologysupporting
confidence: 80%
“…Among them, streptozotocin intracerebroventriculary-treated rats (STZ-icv model) have been recognized as a model that shares major pathological similarities with the human sAD condition, in addition to cognitive decline [57]. Pathological changes found in this model are the consequence of oxidative stress and a brain insulin resistant state induced by icv administration of STZ [58], and an insulin resistant brain state has been proposed as the metabolic core in human sAD [59][60][61].…”
Section: Modelling Of Alzheimer's Diseasementioning
confidence: 99%
“…Neurochemical changes in insulin receptor signalling in the brain as well as cognitive decline in STZicv rat model demonstrate a biphasic time pattern, while structural changes and Aβ and tau pathology develop and progress slowly in a linear manner [57,58]. Such a staging scheme suggests that late changes might correspond to the symptomatic sAD phase in humans [57].…”
Section: Modelling Of Alzheimer's Diseasementioning
confidence: 99%
See 1 more Smart Citation